Securing State’s Asset: Legal Protection of Natural Resources of Oil and Gas - Friasmita, Anisa Devi; Nisa, Farah Hafizha (Lembaga Contrarius Indonesia, 2023)
The legal framework for oil and natural gas activities in Indonesia is established by Law Number 22 of 2001 concerning Oil and Natural Gas, which was officially published in the State Gazette in 2001. SKK Migas, which replaced BP Migas, is responsible for the management of upstream oil and gas activities based on Cooperation Contracts (KKS). The upstream activities are conducted through Cooperation Contracts (KKS) as specified in Article 6 of the Oil and Gas Law. According to Article 1, number 19 of the Oil and Gas Law, a Production Sharing Contract (PSC) refers to a cooperative arrangement that aims to maximize the benefits from exploration and exploitation activities for the state and ensure the welfare of the people.